Internationalization and the Expansion of Islamic Higher Education in Turkiye: Historical Legacies, Policy Shifts, and Mobility Challenges in Theology Programs - Demir, Kerem Alp; AydÄ±n, Selim Efe (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2026)
This article examines the internationalization and expansion of Islamic higher education and theology programs in Turkey. It argues that Turkey represents an important case because its theology education has been shaped by the transformation from Ottoman medrese traditions to modern university-based faculties, secular republican reforms, political Islam, state regulation, and changing geopolitical aspirations. Using a qualitative literature-based method with a thematic and conceptual-critical approach, this study synthesizes scholarly works on Turkish Islamic higher education, curriculum reform, English-medium instruction, scholarship programs, educational diplomacy, governance, and academic mobility. The findings show that internationalization in Turkish theology programs is not merely a technical process of increasing international students, adopting English-medium instruction, or expanding global partnerships. It is also an institutional and epistemological process involving religious identity, curriculum integrity, linguistic plurality, quality assurance, stakeholder participation, and soft power. The article concludes that Islamic higher education requires a context-sensitive model of internationalization that combines academic excellence, religious and ethical identity, intercultural competence, educational diplomacy, and participatory governance.